2021
DOI: 10.1111/cas.14867
|View full text |Cite
|
Sign up to set email alerts
|

Study of the physicochemical properties of drugs suitable for administration using a lymphatic drug delivery system

Abstract: Lymph node (LN) metastasis is thought to account for 20‐30% of deaths from head and neck cancer. The lymphatic drug delivery system (LDDS) is a new technology that enables the injection of drugs into a sentinel LN (SLN) during the early stage of tumor metastasis to treat the SLN and secondary metastatic LNs. However, the optimal physicochemical properties of the solvent used to carry the drug have not been determined. Here, we show that the osmotic pressure and viscosity of the solvent influenced the antitumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 26 publications
(52 reference statements)
4
20
2
Order By: Relevance
“…As shown in a previous study, we found that the optimal ranges of osmotic pressure were greater than for saline and <3,000 kPa. 36 The optimal conditions of osmotic pressure and viscosity presented in this study were not limited to DTX. In the LDDS, a solvent with an osmotic pressure and viscosity of 1,960 kPa and 12 mPa·s would be appropriate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As shown in a previous study, we found that the optimal ranges of osmotic pressure were greater than for saline and <3,000 kPa. 36 The optimal conditions of osmotic pressure and viscosity presented in this study were not limited to DTX. In the LDDS, a solvent with an osmotic pressure and viscosity of 1,960 kPa and 12 mPa·s would be appropriate.…”
Section: Discussionmentioning
confidence: 97%
“…32,33 Preliminary studies have shown that physicochemical ranges were determined by two independent factors: osmotic pressure and viscosity for LDDS. 36 In the present study, we hypothesized that when a chemotherapeutic agent solution with high osmotic pressure and viscosity was given through the LDDS, expansion of lymphatic vessels and sinuses, drug retention, and the subsequent antitumor effect could be controlled. When tumor cells proliferate in the lymphatic sinuses, tumor embolism occurs in the lymphatic sinuses.…”
mentioning
confidence: 96%
“…The LDDS is a local treatment method in which anticancer drugs are injected directly into LNs to target early metastases. 14 , 15 , 16 The LDDS produces a higher drug retention rate and tissue selectivity in LNs compared to systemic chemotherapy and elicits greater antitumor effects. 14 , 16 Assuming clinical application, the amount of drug used is extremely low (1/1000–10,000 of systemic chemotherapy), and side‐effects are minimal.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 , 16 The LDDS produces a higher drug retention rate and tissue selectivity in LNs compared to systemic chemotherapy and elicits greater antitumor effects. 14 , 16 Assuming clinical application, the amount of drug used is extremely low (1/1000–10,000 of systemic chemotherapy), and side‐effects are minimal. Recently, it has been shown that the antitumor effect can be further enhanced by adjusting the anticancer drugs used in LDDS with a highly osmotic, highly viscous solvent.…”
Section: Introductionmentioning
confidence: 99%
“…This often results in insufficient dosage accumulation and retention of the anti-cancer agents required to treat metastasis effectively. In addressing this issue, our group reported a more efficient method for anti-cancer drug delivery to metastatic sites via the lymphatic route [24,29,30]. This delivery route has motivated the design of new nanocomposite-based therapeutic approaches as alternatives to invasive treatment protocols [31,32].…”
Section: Introductionmentioning
confidence: 99%